(untitled) (Innovative professional education, 2023)
The development of motivation in skilled workers in the service sector in training centers involves the formation of values in them to realize the importance of continuous professional development for successful professional activity and career growth. The methods of implementing the pedagogical condition for the development of motivation in vocational education students are analyzed, the most effective methods of motivating the development of professional competence of skilled service workers are identified, namely: explaining the importance of continuous professional development, its social significance and personal value; involvement in the formation of content, forms and methods of teaching; appealing to the professional and life experience of students; encouraging activity and independence in learning; creating situations of feeling of success.